2011 IEEE 11th International Conference on Data Mining 2011
DOI: 10.1109/icdm.2011.79
|View full text |Cite
|
Sign up to set email alerts
|

Improving Product Classification Using Images

Abstract: Abstract-Product classification in Commerce search (e.g., Google Product Search, Bing Shopping) involves associating categories to offers of products from a large number of merchants. The categorized offers are used in many tasks including product taxonomy browsing and matching merchant offers to products in the catalog. Hence, learning a product classifier with high precision and recall is of fundamental importance in order to provide high quality shopping experience.A product offer typically consists of a sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 22 publications
2
18
0
Order By: Relevance
“…Recently, deep learning technology such as CNN was used to extract image features. It was also utilized for image classification and pattern recognition [16][17][18]. Research reported that the performance of a CNN model can be improved when pre-trained and pre-weighted values are used with a large volume of image data such as that of ImageNet [19,20].…”
Section: Image2vec-based Feature Extraction Modelmentioning
confidence: 99%
“…Recently, deep learning technology such as CNN was used to extract image features. It was also utilized for image classification and pattern recognition [16][17][18]. Research reported that the performance of a CNN model can be improved when pre-trained and pre-weighted values are used with a large volume of image data such as that of ImageNet [19,20].…”
Section: Image2vec-based Feature Extraction Modelmentioning
confidence: 99%
“…Although there are a lot of approaches for products matching and classification based on text features, only a few are using image features for the given task. Kannan et al [10] proposed one of the first approaches for product categorization that besides text features uses image features. The approach is based on Confusion Driven Probabilistic Fusion++, which is cognizant of the disparity in the discriminative power of different types of signals and hence makes use of the confusion matrix of dominant signal (text) to prudently leverage the weaker signal (image), for an improved performance.…”
Section: Product Classificationmentioning
confidence: 99%
“…Dataset The latest extraction of WebDataCommons includes over 5 billion entities marked up by one of the three main HTML markup languages (i.e., Microdata, Microformats and RDFa) and has been retrieved from the CommonCrawl 2014 corpus 10 . From this dataset we focus on product entities annotated with Microdata using the schema.org vocabulary.…”
Section: Unstructured Product Offers -Wdc Microdatamentioning
confidence: 99%
“…While some approaches do use computer vision to classify products, they face many challenges such as high training time, low accuracy, requirement of powerful computing resources, etc. [6].…”
Section: Importance and Aim Of The Projectmentioning
confidence: 99%
“…While some products on ecommerce websites are categorized manually, this number is very small [6]. Having millions of products on the website, it is not possible to manually categorize each and every one of them, which is why an automatic classification system becomes of utmost importance for any ecommerce website.…”
Section: Introductionmentioning
confidence: 99%